SEMICLASSICAL CALCULATION OF ENERGY-TRANSFER IN POLYATOMIC-MOLECULES .9. CROSS-SECTIONS FOR HE+CO2(000)-]HE+CO2(NML) AND AR+CO2(000)-]AR+CO2(NML) - Billing, G; Clary, D (1983)
Cross sections for excitation of the asymmetric-stretch vibrational manifold of CO2 in collision with He and Ar have been calculated using a semiclassical collision method and a potential-energy surface constructed from self-consistent field data. The cross sections for collisional energies up to 2.0 eV are compared with those obtained in a molecular-beam experiment. © 1983.